Early Paleogene plant biomes of the Pacific side of Eurasia - Bondarenko, Olesia V.; Utescher, Torsten (Palaeoworld, 2025)
Major plant biome changes in East Asia during the early Paleogene are studied using the Integrated Plant Record vegetation analysis for the first time based on paleobotanical records. The paleobotanical record employed for the reconstruction comprises 110 paleofloras covering the early Paleocene to early Eocene, a time-span of ca. 17 Myr. Our data indicate the presence of more forested conditions over East Asia during the early Paleogene than at present. The early Paleogene vegetation cover in the study area fundamentally differed from modern and was much more homogeneous compared to the modern one. Mixed mesophytic zonal vegetation dominated on the Pacific side of Eurasia during the early Paleogene. Thermophilous mixed mesophytic forests were distributed even at very high latitudes, but at the same time, ecotone between the mixed mesophytic / broadleaved evergreen forests and broadleaved evergreen forest were confined to regions south of 50°N. The proportions of sclerophyllous plants are low in general, even in the mid-latitudes. The localities with open woodlands are all located south of ca. 45°N. The observed vegetation patterns and their changes throughout the early Paleogene in many cases can be correlated with climate patterns and the overall continental paleoclimate evolution as reconstructed from the paleobotanical record. The higher-than-present spatial homogeneity of early Paleogene vegetation coincides with shallow temperature gradients and a significantly more humid regional rainfall pattern over East Asia during the early Paleogene.